(untitled) (Global Journal of Management and Business Research, 2022)
Fusion recipes are mixing and matching of different ingredients from different flavors, cultures, and countries to generate new and innovative recipes. In short, it is a mix and match of different cuisines. Fusion recipes are mixing and matching of different ingredients from different flavors, cultures, and countries to generate new and innovative recipes. In short, it is a mix and match of different cuisines. They are the best mixers of existing recipes. Fusion recipes have been running like a viral recipe on the internet. People are crushing over it like never before but what exactly fusion recipes are? What is the zest of it? Well, fusion simply means authentic recipes.